Peningkatan Keaktifan dan Hasil Belajar Matematika Melalui Strategi Pembelajaran Rotating Trio Exchange (RTE) - Karim, Abdul (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This research aims to increase the activity and learning outcomes of class IX B students at SMPN 5 Rangkasbitung, Lebak Regency on the topic of Curviliniear Solid Figures by implementing the Rotating Trio Exchange (RTE) learning strategy. The research method used is Classroom Action Research consisting of three cycles where each cycle consists of two actions. Research data was obtained from test results, observations, questionnaires and interviews. The research results show that there is an increase in learning outcomes and student activity in each cycle after learning using the Rotating Trio Exchange (RTE) strategy. The average student learning outcome in cycle 1 is 57.33, increasing to 71.50 in cycle 2 and in cycle 3 becomes 72.29 with class completion in cycle 3 76.67%, while the average student activity in cycle 3 reached 80.33% so the research is said successful. The interview results show that students are interested in the RTE learning strategy because it can increase student participation in the learning process.